PARADIGMA TAUHID SEBAGAI BASIS MEWUJUDKAN MODERASI ISLAM DI INDONESIA - Muhammad Alan Juhri (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2020)
Conflict between religious communities, until now, is still a plague that never heals. In fact, in Indonesia itself, not only conflicts between people of different religions, conflicts between religions also often occur. Among Muslims for example, one Muslim group with another Muslim group often conflicts due to differences in understanding. This incident is not uncommon due to mutual self-righteousness. One community considers that the group's understanding is the most correct, while the other community is wrong. Conversely, other communities are also reluctant to be blamed, so it is not surprising that this kind of conflict leads to hostility, dissension, even to violence and murder. This certainly threatens the comfort and harmony of life in Indonesia, and must be eradicated. For this reason, this paper will offer an idea called the â€œtauhidic paradigmâ€. This idea necessitates that everyone truly affirms God (tauhid) and actualizes it in religious life. That is, every religious community must realize and believe that only God should be exalted. While all humans occupy the same and equal position as servants of God, so no one has the right to feel himself superior and better than other servants. So, in the â€œtauhidic paradigmâ€, a servant is not justified to denigrate and denigrate other peoples. Thus, this tauhidic paradigm will certainly play an important role in strengthening the values of tolerance for every religious community in Indonesia, so that with tolerance that Islamic moderation in Indonesia can be realized.